2021
DOI: 10.1039/d1ta02953c
|View full text |Cite
|
Sign up to set email alerts
|

Carbocatalytic ozonation toward advanced water purification

Abstract: Carbon-based catalytic ozonation is state-of-the-art technology with high oxidation capabilities for wastewater remediation, taking advantage of the synergies of direct ozone oxidation and the generated reactive oxygen species (ROS). Replacing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 309 publications
(350 reference statements)
0
15
0
Order By: Relevance
“…•− , surface-bound • OH, and surfaceactivated PS complexes is currently unknown, whereas that of *O ad is 2.43 V [72]. As for other distinctions between the systems, the formation of SO 4…”
Section: Biochar Active Sites Involvement and Produced Rosmentioning
confidence: 98%
See 2 more Smart Citations
“…•− , surface-bound • OH, and surfaceactivated PS complexes is currently unknown, whereas that of *O ad is 2.43 V [72]. As for other distinctions between the systems, the formation of SO 4…”
Section: Biochar Active Sites Involvement and Produced Rosmentioning
confidence: 98%
“…From these results and upon studying the effects of catalytic parameters, it can be concluded that the electron-rich C=O active sites are of paramount importance in adsorbing dissolved O 3 , then initiating its rapid decomposition to produce • O 2 − that will cause the oxidation of C=O groups to O-C=O. Moreover, chromene-like and pyrone-like OFGs can reactively react with O 3 through the Criegee mechanism to form H 2 O 2 , which then reacts with the surface-active sites of carbonaceous catalyst or O 3 to yield • OH [72]. In addition, O 3 adsorption and decomposition to form • OH prefers the Lewis acid sites on the biochar surface [73,74].…”
Section: O 3 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The development of AOPs in the last decade (a) and the technical evolution of carbon-based AOPs for water decontamination (b). [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] following representative publications: Yu et al, 50 Duan et al, 51 Liu et al, 52 and Wang et al 20 2.1.1. Activated carbon.…”
Section: Aops Owing To Their Unique Advantages Compared With Metalbas...mentioning
confidence: 99%
“…As a consequence, we only briefly summarize some recent advances here without focusing on the preparation methods of carbocatalysts and their properties. For more information, the readers are recommended to refer to the following representative publications: Yu et al , 50 Duan et al , 51 Liu et al , 52 and Wang et al 20…”
Section: Metal-free Catalystsmentioning
confidence: 99%